Silicon carbide benefits and advantages for power electronics circuits and systems - Elasser, A.; Chow, T.P. (Proceedings of the IEEE, 2002)
Silicon offers multiple advantages to power circuit designers, but at the same time suffers from limitations that are inherent to silicon material properties, such as low bandgap energy, low thermal conductivity, and switching frequency limitations. Wide bandgap semiconductors, such as silicon carbide (SiC) and gallium nitride (GaN), provide larger bandgaps, higher breakdown electric field, and higher thermal conductivity. Power semiconductor devices made with SiC and GaN are capable of higher blocking voltages, higher switching frequencies, and higher junction temperatures than silicon devices. SiC is by far the most advanced material and, hence, is the subject of attention from power electronics and systems designers. This paper looks at the benefits of using SiC in power electronics applications, reviews the current state of the art, and shows how SiC can be a strong and viable candidate for future power electronics and systems applications.